CRIMINAL LIABILITY OF STATE OFFICIALS IN HUMAN TRAFFICKING CASES TO CAMBODIA AND EFFORTS TO REPATRIATE VICTIMS - Muhammad Dewanto Adi Saputra; Kayus Kayowuan Lewoleba (RADJA PUBLIKA, 2026)
Human trafficking to Cambodia constitutes a transnational crime involving cross-border criminal networks and, in several cases, state officials who abuse their authority. This situation creates significant challenges for law enforcement and the legal protection of victims, particularly during the repatriation process. This study aims to analyze the criminal liability of state officials involved in human trafficking to Cambodia and to examine the effectiveness of legal protection in the implementation of victim repatriation. This research employs a normative juridical method with a descriptive qualitative approach using statutory and case approaches. The findings indicate that the criminal liability of state officials is regulated under Law Number 21 of 2007 on the Eradication of the Crime of Human Trafficking and is further strengthened by Law Number 1 of 2023 concerning the Indonesian Criminal Code. However, its implementation remains ineffective because law enforcement has not fully addressed the involvement of intellectual actors and state officials participating in these crimes. Furthermore, the repatriation process continues to face challenges, including limited inter-agency coordination, inadequate diplomatic capacity, and the suboptimal fulfillment of victims' rights. Therefore, strengthening law enforcement and improving the victim repatriation mechanism are necessary to ensure more effective legal protection for victims.